Everybody Brush! Consumer Satisfaction with a Tooth Decay Prevention Program - Cunha-Cruz, Joana; Huebner, Colleen E.; Ludwig, Sharity; Dysert, Jeanne; Mitchell, Melissa; Allen, Gary; Shirtcliff, R. Mike; Scott, JoAnna M.; Milgrom, Peter (Frontiers in Public Health, 2017)
Introduction: Twice-daily caregiver-supervised toothbrushing with fluoridated toothpaste is an effective and widely recommended strategy to prevent tooth decay in children. Qualitative research suggests low-income caregivers know the recommendation but would benefit from toothbrushing supplies and advice about how to introduce this health behavior especially as the child becomes older and asserts autonomy to do it “myself.” Our objective is to assess consumer satisfaction with the evidence-based theory-informed campaign and usefulness of materials that were home delivered. The focus of the evaluation was families with children <36 months of age because of the high incidence of disease in this population. Methods: A dental care organization designed and implemented Everybody Brush! in 3 counties of Central Oregon. Participants were families of Medicaid-insured children <21 years of age. Participants were randomly assigned to one of 3 study groups: test (supplies, voice/printed messages, telephone support), active (supplies) and a waitlist control. Program materials were in English and Spanish. Caregivers of children <36 months were interviewed at the beginning and end of the program. Results: A total of 83,148 toothbrushing kits were mailed to 21,743 families. In addition, 93,766 printed messages and 110,367 recorded messages were sent to half of the families. Caregivers were highly satisfied. On a global rating scale from 0 to 10 (worst to best program possible), they rated the program 9.5 on average (median: 10, SD 0.9). On a scale from 0 to 10 (not at all to very useful), mean ratings for usefulness of the toothbrushing supplies was 9.5 (SD=1.5), for the printed postcard messages was 7.2 (SD 3.6) and for the voice telephone messages was 6.5 (SD 3.9). Discussion: A dental care organization carried out a complex community intervention designed to address excess tooth decay among low-income children. Caregivers were highly satisfied with the Everybody Brush! program and toothbrushing supplies were considered the most useful, followed by printed messages. Voice telephone messages were rated least useful. Further evaluation of the impact of the program on toothbrushing behavior and dental care utilization is underway.